Design and Implementation of Protocols Association Scbeme on Iu-PS Interface in TD-SCDMA Network - Rui Li; Zhizhong Zhang (Dianxin kexue)
In order to identify the user traffic and analysis the user behavior on Iu-PS interface in TD-SCDMA network, the signaling plane protocol stack and the service plane protocol stack of Iu-PS interface were analysed and a scheme that associated with signaling plane protocols and service plane protocols were designed. In view of the low processing efficiency of signaling and service monitoring system and inability to associate with both signaling and service data, using the enhanced Hash algorithm and timeout processing technology,a protocols association scheme with synthetic solution of call detail record in both signaling and service plane were designed, which based on a key words association method. The scheme improves the efficiency of data processing, implements the effective association between signaling data and service data, and also lays the foundation for traffic identification and user behavior analysis. The accuracy and feasibility of this protocol association scheme has been validated by the real network testing, and this scheme has the important significance to promote in the field of mobile Internet traffic analysis.